(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2003)
A new genus and species of diapsid reptile is described. The specimen was collected from the Anisian (Middle Triassic) succession of Monte Prà della Vacca (Kühwiesenkopf) in the Dolomites of Braies (Bolzano/Bozen, Northern Italy). Despite being incomplete, the specimen shows enough characters to allow its placement within Lepidosauriformes, close to the Middle Jurassic genus Marmoretta. The importance of this find lies in the great rarity of lepidosauriforms of Anisian age, an epoch approximating the appearance of the first members of the true Lepidosauria (rhyncocephalians and squamates). The new genus may thus add knowledge to the diversity of early lepidosaurians. Some characters of the skeleton, mainly of the forelimb, suggest a terrestrial, perhaps arboreal life style.